Phase variation of the opacity outer membrane protein controls invasion by Neisseria gonorrhoeae into human epithelial cells. - Makino, S (1991)
Neisseria gonorrhoeae is a facultative intracellular bacterium capable of penetrating into certain human epithelial cell types. In order to identify gonococcal factors essential for invading Chang human conjunctiva cells, a gentamicin selection assay for the quantification of viable intracellular bacteria was used in conjunction with microscopy. The results demonstrate a correlation between the invasive behaviour of gonococci and the expression of Opa proteins, a family of variable outer membrane proteins present in all pathogenic Neisseria species. However, only particular Opa proteins supported invasion into Chang cells as indicated by the use of two unrelated gonococcal strains. Invasion was sensitive to cytochalasin D, and strong adherence mediated by the Opa proteins appeared to be essential for the internalization of gonococci. In contrast pili, which also conferred binding to Chang conjunctiva cells, did not support cellular invasion but rather were inhibitory.